Exercise pressor reflex in health and diseases: Animal studies - Satoshi Koba (Japanese Society of Physical Fitness and Sports Medicine, 2015)
A reflex originating in exercising skeletal muscle contributes to sympathoexcitation during exercise. This muscle-based reflex is termed the exercise pressor reflex (EPR). In this review, mechanisms underlying activation of the EPR are examined based on findings mainly obtained from cat studies. Specifically, roles played by chemical and mechanical stimuli due to contraction in increasing discharges of muscle afferent fibers are discussed. Roles metabolic byproducts play in stimulating and sensitizing muscle afferents are also examined. Central cardiovascular sites involved in activation of the EPR are investigated. In this review, moreover, mechanisms by which the EPR function becomes abnormal in heart failure and hypertension are discussed on the basis of experimental data mainly provided by rat studies. In heart failure, the muscle metaboreflex is attenuated while the mechanoreflex is enhanced. In hypertension, both the muscle metabo- and mechano- reflexes are enhanced. Peripheral factors leading to EPR dysfunction in these pathological conditions are examined.